2009
DOI: 10.1016/j.cognition.2009.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Core knowledge and its limits: The domain of food

Abstract: Adults, preschool children, and nonhuman primates detect and categorize food objects according to substance information, conveyed primarily by color and texture. In contrast, they perceive and categorize artifacts primarily by shape and rigidity. The present experiments investigated the origins of this distinction. Using a looking time procedure, Experiment 1 extended previous findings that rhesus macaques (Macaca mulatta) generalize learning about novel food objects by color over changes in shape. Six additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 74 publications
(132 reference statements)
3
36
0
Order By: Relevance
“…One and the same food can be associated to a variety of visual or tactile shapes: the shape of the original ingredients, the shape of the packed food, and then of the cooked food on the plate, the shape of the eaten piece of food in the spoon, and finally its changing shape in the mouth. The absence of statistically relevant association between kinds of foods and kinds of shapes is confirmed by various studies (Santos et al 2001;Shutts et al 2009) showing that infants and macaques discount information about shapes and privilege colors for foods, by contrast with non-food objects.…”
Section: Introductionsupporting
confidence: 59%
“…One and the same food can be associated to a variety of visual or tactile shapes: the shape of the original ingredients, the shape of the packed food, and then of the cooked food on the plate, the shape of the eaten piece of food in the spoon, and finally its changing shape in the mouth. The absence of statistically relevant association between kinds of foods and kinds of shapes is confirmed by various studies (Santos et al 2001;Shutts et al 2009) showing that infants and macaques discount information about shapes and privilege colors for foods, by contrast with non-food objects.…”
Section: Introductionsupporting
confidence: 59%
“…Given its ecological importance, there may be early-emerging adaptations that support complex reasoning in the food domain. Yet, past research has revealed that human infants are surprisingly inept at categorizing and selecting appropriate foods (4,5). However, these studies did not consider the importance of social aspects of food choice.…”
mentioning
confidence: 99%
“…Indeed, children under 2 y of age are the most likely age group to accidentally poison themselves (24). Additionally, although adults, older children, and even adult monkeys rely on different perceptual properties to make inferences about foods and about artifacts (e.g., using color when reasoning about foods, shape when reasoning about artifacts), human infants do not (5,(27)(28)(29)(30)(31)(32)(33)(34)(35). Because human infants have historically relied on caregivers to provide safe and nutritious diets, they may not need to have mechanisms in place for reasoning about food.…”
mentioning
confidence: 99%
“…First, this literature has traditionally focused on food preference, but not evaluative categorization (which may also be integral to the reasoning behind children's food choices). Second, this literature has traditionally focused on how modeling guides early food preferences (Frazier et al, 2012; Hamlin & Wynn, 2012; Hendy & Raudenbush, 2000; Shutts et al, 2009; Shutts et al, 2010), but not the influence of trust in testimony. An exception is a study that found that children's jelly bean selection is affected by adults' assessments of the jelly bean flavors' palatability (Lumeng et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Examining children's trust in testimony in regards to food is also an especially critical issue given the ecological importance of this domain in children's lives (see Shutts, Condry, Santos, & Spelke, 2009; Shutts et al, 2012; Siegal, 1995; Rozin, 1990). It is estimated that adults make over 200 food and beverage choices a day (Wansink & Sobal, 2007).…”
Section: Children's Trust In Testimonymentioning
confidence: 99%